Magnetic frustration and magnetocaloric effect in AlFe2−xMnxB2 (x = 0–0.5) ribbons. (20th July 2015) - Du, Qianheng; Chen, Guofu; Yang, Wenyun; Wei, Jianzhong; Hua, Muxin; Du, Honglin; Wang, Changsheng; Liu, Shunquan; Han, Jingzhi; Zhang, Yan; Yang, Jinbo
Abstract: The crystal structure and magnetic properties of AlFe2− x Mn x B2 ( x = 0–0.5) compounds were investigated. With increasing Mn content, the magnetic properties of these compounds evolve gradually and the lattice parameters change continuously: Curie temperature ( T c ) decreases from 312 K ( x = 0) to 220 K ( x = 0.5) and a new phase transition from the ferromagnetic state (FM) to spin-glass state (SPG) appears upon cooling. The lattice shrinks in the ab plane while it expands in the c direction. The formation of re-entrant SPG around 50 K was studied via temperature dependent ac and dc magnetization as well as the initial magnetization curves in 5 K. The reason for this glass state is the triangular configuration of magnetic atoms and the antiferromagnetic interactions introduced by Mn substitutions. The Curie transition leads to a conventional magnetocaloric effect (MCE). The Mn doping leads to a decrease in the MCE near room temperature, but there is a plane in entropy change (Δ S ) for the x = 0.1 compound under low field which makes these compounds good candidates to produce composites used for magnetic refrigeration application in a wide temperature span.